2015
DOI: 10.31768/2312-8852.2015.37(1):58-63
|View full text |Cite
|
Sign up to set email alerts
|

Сd44+/Cd24− Markers of Cancer Stem Cells in Patients With Breast Cancer of Different Molecular Subtypes

Abstract: Aim: To determine frequency of tumors with immunohistochemical markers of cancer stem cells (CSC) CD44+/CD24− in patients with breast cancer (BC) of different molecular subtype and to evaluate their prognostic value. Object: Surgical material of 132 patients with BC stage I–II, age from 23 to 75 years, mean age — 50.2 ± 3.1 years was studied. Methods: Clinical, immunohistochemical (expression CD44+/CD24−), morphological, statistical. Results: BC is characterized by heterogeneity of molecular subtypes and expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 30 publications
1
20
0
Order By: Relevance
“…This agrees with a previous study showing that patients with CSC markers CD44(+)/CD24(−) had a lower survival rate, while patients without this subpopulation had a higher survival rate in basal-like breast cancer. 89 Some studies showed that CD44 expression was positively correlated with the metastasis of breast carcinoma, 75 but others reported opposite results. 90 Martin and Jiang found that CD44 was markedly reduced in patients with ductal breast cancer with metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…This agrees with a previous study showing that patients with CSC markers CD44(+)/CD24(−) had a lower survival rate, while patients without this subpopulation had a higher survival rate in basal-like breast cancer. 89 Some studies showed that CD44 expression was positively correlated with the metastasis of breast carcinoma, 75 but others reported opposite results. 90 Martin and Jiang found that CD44 was markedly reduced in patients with ductal breast cancer with metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Different subtypes of BC constitute different proportion of BCSCs contributing to different disease outcome. Among the BC subtypes, the highest amount of CSCs was observed in patients with TNBC (basal) subtype and has been correlated with its aggressiveness 64…”
Section: Breast Cancer Stem Cells (Bcscs): the Troublemakersmentioning
confidence: 99%
“…The interaction between HA and CD44 also contributes to the resistance of HER-positive breast cancer cells to trastuzumab 20 and is associated with poor prognosis in breast cancer patients. 30 33 Recent studies reported that the binding of HA to CD44 can modulate the activity of EGFR family members. 14 The serum CD44 concentration was a significant predictor of overall survival for patients with HER-2-positive breast cancer, which suggested that CD44 should be investigated further for its potential as a prognostic biomarker.…”
Section: Discussionmentioning
confidence: 99%